Remarks by World Bank Group President David Malpass at World Bank Group 2022 Spring Meetings Ministerial Roundtable for Support to Ukraine - Malpass, David (World Bank, World Bank, 2022)
These remarks were delivered by World Bank Group President David Malpass at World Bank Group 2022 Spring Meetings Ministerial Roundtable for Support to Ukraine on April 21, 2022. He said that he has been deeply horrified and shocked by Russia’s invasion of Ukraine, the atrocities committed against the civilian population, and the loss of life and livelihoods for millions of Ukrainians. He mentioned that since the invasion, the World Bank Group has provided fast-disbursing financial support to help the government provide critical services, pay wages for hospital workers, public servants, and the elderly. He insisted that It will be important for all partners to continue coordinating their support for Ukraine’s budget needs. He described that the World Bank Group is working toward three phases of the recovery effort of relief, recovery, and resilience. He said that as the war continues, the World Bank Group will work to build confidence in Ukraine’s financial, monetary, and fiscal institutions, fostering currency stability as they go forward. He mentioned that rebuilding will take hard work, determination, and struggle, but he remains optimistic. He concluded by saying that with our collective support, Ukraine can achieve a brighter future.